Clinical Evaluation of Vacha Rhizome (Acorus Calamus Linn) as Memory Booster in Children (AYUSHDHARA, 2023)
Medhya Rasayana, a rejuvenation therapy which comes under Kamya Rasayana which is one among 5 types of Rasayana. Vacha is one among such drugs which has Smrutivardhan activity, Smruti vardhana activity is comparable with memory boosting/enhancing activity. Medhya activity is inclusive of Smruti and hence in Ayurveda Medhya drugs do include one of their therapeutic aspects as Smruti vardhana.Two groups of 20 volunteers are selected and Group A are given capsules containing Vacha rhizome fine powder each with a dose of 250mg twice a day for 48 days empty stomach and follow up was done on 96th day. Group B received placebo of cap Dextrin 250mg for same duration and time as of group A.Vacha rhizome Churna show the better memory boosting activity in children in comparison with Dextrin. Statistically significant results were found in group A, observed between the results of 0th day and 96th day with P